2012
DOI: 10.4172/2153-0769.1000115
|View full text |Cite
|
Sign up to set email alerts
|

Sex Dependency of Human Metabolic Profiles Revisited

Abstract: Background: Human metabolic profiles based on the four compound classes acylcarnitines, amino acids, hexoses and phospho and sphingolipids were found to exhibit a significant sex difference in a previous study. We set out to verify this result in a geographically distinct cohort with an adequately sized sample by analyzing the same set of biomarkers and various additional biogenic amines not hitherto considered in such studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Among obtained metabotypes, it is interesting to note that the level of all acylcarnitines was higher in castrated males than in intact gilts. This result already has been observed comparing plasma and serum concentration of acylcarnitines in men and women (Slupsky et al, 2007;Reuter et al, 2008;Mittelstrass et al, 2011;Siegert et al, 2012). Mihalik et al (2010) reported that increased levels of several acylcarnitines were pres-ent in the plasma of obese individuals and in men and women with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Among obtained metabotypes, it is interesting to note that the level of all acylcarnitines was higher in castrated males than in intact gilts. This result already has been observed comparing plasma and serum concentration of acylcarnitines in men and women (Slupsky et al, 2007;Reuter et al, 2008;Mittelstrass et al, 2011;Siegert et al, 2012). Mihalik et al (2010) reported that increased levels of several acylcarnitines were pres-ent in the plasma of obese individuals and in men and women with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 57%
“…A total of 132 out of 186 analyzed metabolites (71%) passed the quality control step. It is worth mentioning that the CV% threshold that was used in our study (CV% = 20) is more stringent than that was used by previous studies performed with the same AbsoluteIDQ metabolomic platform in human plasma or serum (CV% = 25 or 30; Mittelstrass et al, 2011;Siegert et al, 2012). In this way, we wanted to be very conservative and prefiltered the data set to maximize the potentials of the statistical pipelines that rely only on the metabolites less affected by analytical or technical factors that could increase the variability in the quantification.…”
Section: Metabolomic Datamentioning
confidence: 98%
“…Strengths of this study include the biochemical analyses in a relatively large cohort of male and female mice, which enabled us to analyse the effects of genotype, sex and their interaction. Sexual dimorphism in plasma acylcarnitine concentrations have been reported, [30][31][32] but effects of sex on tissue (acyl)carnitine levels are unexplored. We observed sexual dimorphism for the levels of many acylcarnitines in particular in the kidney, an organ known to have high degree of sexually dimorphic gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed the association of age with metabolites by linear regression, in which the metabolite concentration was extrapolated to age zero years and was set to 100%. In addition, the interaction of age with sex was checked due to indications of sexual dimorphism in the metabolome [20]. This was done by adding an interaction term between age and sex.…”
Section: Statistical Analysesmentioning
confidence: 99%